Metabolic recovery from submaximal exercise in hypoxia acclimated high altitude deer mice (Peromyscus maniculatus) - Dessureault LM; Tod RA; McClelland GB (Elsevier, 2024)
Animals living at high-altitude are faced with unremitting low oxygen availability. This can make it difficult to perform daily tasks that require increases in aerobic metabolism. An activity important for survival is aerobic locomotion, and the rapid recovery of muscle metabolism post exercise. Past work shows that hypoxia acclimated high-altitude mice (Peromyscus maniculatus) have a greater reliance on carbohydrates to power exercise than low altitude mice. However, it is unclear how quickly after aerobic exercise these mice can recovery and replenish muscle glycogen stores. The gastrocnemius muscle of high-altitude deer mice has a more aerobic phenotype and a greater capacity to oxidize lipids than low altitude deer mice. This suggests that high altitude mice may recover more rapidly from exercise than their lowland counterparts due to a greater capacity to support glycogen replenishment using intramuscular triglycerides (IMTG). To explore this possibility, we used low- and high-altitude native deer mice born and raised in common lab conditions and acclimated to chronic hypoxia. We determined changes in oxygen consumption following 15 min of aerobic exercise in 12% O2 and sampled skeletal muscles and liver at various time points during recovery to examine changes in key metabolites, including glycogen and IMTG. We found depletion in glycogen stores during exercise only in lowlanders, which returned to resting levels following 90 min of recovery. In contrast, IMTG did not change significantly with exercise or during recovery in either population. These data suggest that exercise recovery is influenced by altitude ancestry in deer mice.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3101 Biochemistry and Cell Biology; 31 Biological Sciences; 3109 Zoology; 3005 Fisheries Sciences; Physical Activity; Animals; Peromyscus; Muscle, Skeletal; Altitude; Glycogen; Physical Conditioning, Animal; Hypoxia; Oxygen Consumption; Acclimatization; Male; Triglycerides; Liver